Political Culture and Judicial Research - Joel B. Grossman; Austin Sarat (Washington University Law Quarterly, 1971)
In what ways does a legal system respond to demands from the political system? How and why are these demands made to the legal system? How are they transformed into policy outputs? And how do these outputs affect the processes of change and the maintenance of stability? Our purpose in this Article is to suggest an approach to research on these questions. Specifically, we will suggest ways in which the concept of “political culture” can be used to sensitize and guide judicial research to a better understanding of environmental influences.